C52 THE BIG FOUR: RESPIRATORY FAILURE, RENAL INSUFFICIENCY, HAEMORRHAGE AND SEPSIS, HOW DO THEY IMPACT ON CICU PATIENT?. (18th May 2022) - Canovi, L; Zanarelli, L; Cardelli, L; Dal Passo, B; Frascaro, F; Piscitelli, L; De Carolis, B; Gibiino, F; Vitagliano, A; Sciarra, F; Zagnoni, S; Pallotti, M; et al.
Abstract: Background: The current rise in life expectancy in the general population leads to changes in baseline characteristics of Cardiac Intensive Care Unit (CICU) patients, increasing the risk of non–cardiac complications during the hospitalization. Objectives: Evaluate epidemiology and prognostic impact of major non–cardiac complications (respiratory failure, renal insufficiency, haemorrhage and sepsis) during CICU stay. Methods: Retrospective analysis of CICU patients at Ospedale Maggiore of Bologna between March and November 2021. Results: Baseline characteristics, cardiovascular risk factors and comorbidities of the patients are reported in Table 1. During the CICU stay, 19.7% of patients suffered from acute respiratory failure, needing for ventilation; 15.0% had renal insufficiency (considered as need for haemodialysis, glomerular filtration rate according to Cockcroft–Gault < 60 ml/min, serum creatinine rise > 25% from baseline); 1.8% reported major haemorrhages (defined as serum haemoglobin < 8 g/dl or need for blood transfusion); 1.7% developed sepsis (positive blood cultures). Mean CICU stay for complicated patients was 6 days, intra–CICU mortality was 1.7% (8 deaths) and 30–days mortality was 7.0% (32 deaths). At univariate logistic regression analysis, acute respiratory failure was the only complication associated with a statistically relevant increase in 30–days mortality (OR 2.37, CI 95%, 1.05–5.34; p = 0.038), although, also the other complications had a negative prognostic effect: haemorrhage (OR 1.58, CI 95%, 1.77–14.16; p = 0.681), renal insufficiency (OR 1.47, CI 95%, 0.56–3.87; p = 0.432) and sepsis (OR 1.25, CI 95%, 0.33–5.87, p = 0.850). Conclusions: Epidemiology and baseline characteristics of CICU patients are changing. Older age and frailty make non–cardiac complications more likely to happen. Acute respiratory failure has the worst prognostic effect on mortality. This fact suggests that CICU Cardiologists should improve their management of these major non–cardiac complications.